Multi-Modality Imaging: A Software Fusion and Image-Guided Therapy Perspective - Birkfellner, Wolfgang; Figl, Michael; Furtado, Hugo; Renner, Andreas; Hatamikia, Sepideh; Hummel, Johann (Frontiers in Physics, 2018)
With the introduction of computers in medical imaging, which were popularized with the presentation of Hounsfield’s ground-breaking work in 1971, numerical image reconstruction and analysis of medical images became a vital part of medical imaging research. While mathematical aspects of reconstruction dominated research in the beginning, a growing body of literature attests to the progress made over the past 30 years in image fusion. This article describes the historical development of non-deformable software-based image co-registration and it’s role in the context of hybrid imaging and provides an outlook on future developments.